Performance Improvement for Correlated 4x4 MIMO-OFDM Systems by Generalized Prefix Approach - Cooklev, Todor; Doğan, Hakan; Yıldız, Hakan; ACAR, YUSUF (IEEE, 345 E 47Th St, New York, Ny 10017 Usa, 2013)
Antenna correlation limits the multiplexing gain achieved by practical MIMO-OFDM systems and degrades the performance significantly. Recently, investigations are focused to reduce the antenna correlation by the designing new antenna structures. Differently, in this paper, we propose the generalized prefix approach to solve problem for correlated MIMO-OFDM system. It is shown that the proposed generalized prefix for 4x4 MIMO-OFDM exhibits a gain of about 8 dB over the conventional 4x4 MIMO-OFDM system at BER = 10(-4)
Keywords: Generalized prefix; orthogonal frequency-division multiplexing (OFDM); multiple-input multiple-output (MIMO); channel correlation